2022
DOI: 10.2147/nss.s379252
|View full text |Cite
|
Sign up to set email alerts
|

All-Cause Mortality in People with Co-Occurring Insomnia Symptoms and Sleep Apnea: Analysis of the Wisconsin Sleep Cohort

Abstract: Purpose Insomnia symptoms and sleep apnea frequently co-occur and are associated with worse sleep, daytime function, mental health and quality of life, compared to either insomnia or obstructive sleep apnea (OSA) alone. This study aimed to investigate the association of symptoms of co-morbid insomnia and sleep apnea (COMISA) with all-cause mortality. Patients and Methods Wisconsin Sleep Cohort data were analysed to assess potential associations between COMISA symptoms a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 59 publications
(110 reference statements)
0
15
0
Order By: Relevance
“…However, analysing 5236 participant data from the same cohort they demonstrated an increased risk of all‐cause mortality in those with COMISA compared with no insomnia/OSA 42 . The same team demonstrated similar findings from the Wisconsin Sleep Cohort when reviewing symptoms of COMISA 43 . Although COMISA only had a prevalence rate of 2%–3% in the SHHS, the negative cardiovascular effects and mortality risk strengthen the need for effective treatments for both when they co‐exist.…”
Section: Insomniamentioning
confidence: 74%
See 1 more Smart Citation
“…However, analysing 5236 participant data from the same cohort they demonstrated an increased risk of all‐cause mortality in those with COMISA compared with no insomnia/OSA 42 . The same team demonstrated similar findings from the Wisconsin Sleep Cohort when reviewing symptoms of COMISA 43 . Although COMISA only had a prevalence rate of 2%–3% in the SHHS, the negative cardiovascular effects and mortality risk strengthen the need for effective treatments for both when they co‐exist.…”
Section: Insomniamentioning
confidence: 74%
“…42 The same team demonstrated similar findings from the Wisconsin Sleep Cohort when reviewing symptoms of COMISA. 43 Although COMISA only had a prevalence rate of 2%-3% in the SHHS, the negative cardiovascular effects and mortality risk strengthen the need for effective treatments for both when they co-exist. At least one study where patients were randomized to receive either CBT-I followed by PAP, self-monitoring followed by CBT-I concurrent with PAP, or self-monitoring followed by PAP only, has demonstrated that concomitant PAP treatment for OSA and CBT-I may accelerate treatment outcomes.…”
Section: Insomniamentioning
confidence: 99%
“…Regarding phenotypes, the data suggest various clusters in which some OSA patients are asymptomatic, some have comorbid insomnia and some have daytime sleepiness (Ye et al, 2014). Of note, OSA patients with hypersomnia as well as comorbid insomnia (Lechat et al, 2022) are thought to be at cardiovascular risk, suggesting that only a subset of OSA patients may experience improvements in cardiovascular risk when treated for OSA. Therefore, recognition of OSA endophenotypes is challenging the "one-size-fits-all" approach of giving nasal CPAP to all OSA patients regardless of mechanism or symptoms (Bosi et al, 2017;.…”
Section: Therapeuticmentioning
confidence: 99%
“…COMISA generally experience worse objective sleep quality/fragmentation, daytime function [12,18], and higher rates of cardiovascular disease [27,29], compared to people with insomnia-alone [7 && ,8]. Three recent studies in population-based cohorts have investigated the association between COMISA and all-cause mortality over 10-20 years of follow-up [27,30,31]. In all three studies, those with COMISA experienced a 47-71% increased risk of mortality in adjusted models compared to people with neither insomnia nor sleep apnea (Table 1).…”
Section: Key Pointsmentioning
confidence: 99%
“…Three recent studies in population-based cohorts have investigated the association between COMISA and all-cause mortality over 10–20 years of follow-up [27,30,31]. In all three studies, those with COMISA experienced a 47–71% increased risk of mortality in adjusted models compared to people with neither insomnia nor sleep apnea (Table 1).…”
Section: Consequences Of Comisamentioning
confidence: 99%